Educational potential of “Foreign Language” course to develop soft skills of technical students - Svetlana G. Menshenina; Polina G. Labzina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Currently the relevance of the development of students’ universal competencies (soft skills) along with the formation of their professional (hard skills) skills is determined by employers’ requirements, rapidly changing labor market and terms of professional activity. The article deals with the students of technical majors soft skills developmentin course foreign language instruction. The authors analyze the essence and the concept of soft skills in frames of foreign language university training. The authors highlight that soft skills development occurs through focused and purposeful work on critical, system and analytical thinking skills. A special course of the discipline "Foreign Language" is designed by the authors. The preliminary results of the experimental work demonstrate that positive dynamics of skills development has been observed.